Rhabdochona angusticaudata sp. n. (Nematoda: Rhabdochonidae) from the Japanese eel Anguilla japonica, and new records of some other nematodes from inland fishes in Japan - Moravec, Frantisek; Nagasawa, Kazuya (Folia parasitologica, 2018)
Collections of parasitic nematodes of fishes from some freshwater and brackish-water localities in Honshu, Shikoku and Hokkaido, Japan, carried out in 1996-2009, yielded the following eight species: Hysterothylacium haze (Machida, Takahashi et Masuuchi, 1978) (Anisakidae), Paraquimperia sp., Pingus sinensis Hsü, 1933 (both Quimperiidae), Heliconema anguillae Yamaguti, 1935 (Physalopteridae), Rhabdochona angusticaudata sp. n., Rhabdochona zacconis Yamaguti, 1935 (both Rhabdochonidae), Ascarophis arctica Polyanskiy, 1952 (Cystidicolidae) and Eustrongylides sp. larvae (Dioctophymatidae). The new species, R. angusticaudata sp. n., described from the intestine of the Japanese eel Anguilla japonica Temminck et Schlegel in the Renjoji River, Shikoku, is mainly characterised by the presence of 14-16 anterior prostomal teeth, non-bifurcated deirids with rounded ends, the length of the left spicule (300-384 µm long), the right spicule with a dorsal barb and non-filamented eggs. The species of Paraquimperia Baylis, 1934 and A. arctica are reported from Japan for the first time. Based on light and scanning electron microscopical examinations, some new morphological data on H. haze, H. anguillae, R. zacconis and A. arctica are provided.
Keywords: Hokkaido; Animals; freshwater fish; Thelazioidea; Female; Prevalence; ženské pohlaví; Ascaridida Infections; Pingus; Ascaridida; Spiruroidea; nemoci ryb; infekce hlísticemi řádu Spirurida; infekce hlísticemi řádu Ascaridida; Fish Diseases; Fishes; Heliconema; Honshu; Animal Distribution; Japonsko; ryby; prevalence; Anguilla; Japan; Paraquimperia; Hysterothylacium; Male; Spirurida Infections; zvířata; mužské pohlaví; parasitic nematode; Shikoku; rozšíření zvířat; Ascarophis